Examining The Role Of Leadership Style, Motivation, and Work Environment In Enhancing Employee Morale - Thomas Epi Adi Putra; Moh Imron (Generate Digital Publishing, 2026)
Objective: This study aims to analyze the influence of leadership style, motivation, and work environment on employee morale at CV Devdan Industries. This research was conducted to provide a more comprehensive understanding of the factors that influence employee morale within the organization. Research Design & Methods: This study employed a quantitative approach, collecting data through the distribution of questionnaires to all 90 employees of CV Devdan Industries. Saturated sampling was used as the sampling technique. Data were analyzed using multiple linear regression analysis. Before testing the hypotheses, the data were subjected to validity, reliability, and classical assumption tests. Findings: The results of the study showed that leadership style and motivation had a positive and significant impact on employee morale. This finding indicates that effective leadership and high work motivation can increase employee enthusiasm, engagement, and responsibility at work. Meanwhile, the work environment did not significantly impact employee morale, indicating that the work environment is not a primary factor influencing morale in the context of this study. Implications & Recommendations: This research offers practical implications for companies to focus more attention on improving leadership quality and employee motivation through effective communication, rewards, regular performance evaluations, and employee competency development. Future research is recommended to include other variables, such as compensation, organizational culture, and job satisfaction, to gain a more comprehensive understanding of the factors influencing employee morale. Contribution & Value Added: This research makes a theoretical contribution by strengthening the relevance of Human Capital Theory and Two-Factor Theory in explaining employee morale. Furthermore, this study also provides empirical evidence regarding the role of leadership style and motivation as dominant factors in improving employee morale in the industrial sector.